Primary quantum thermometry of mm-wave blackbody radiation via induced state transfer in Rydberg states of cold atoms - Noah Schlossberger; Andrew P. Rotunno; Stephen P. Eckel; Eric B. Norrgard; Dixith Manchaiah; Nikunjkumar Prajapati; Alexandra B. Artusio-Glimpse; Samuel Berweger; Matthew T. Simons; Dangka Shylla; William J. Watterson; Charles Patrick; et al. (Physical Review Research)
Rydberg states of alkali-metal atoms are highly sensitive to electromagnetic radiation in the GHz-to-THz regime because their transitions have large electric dipole moments. Consequently, environmental blackbody radiation (BBR) can couple Rydberg states together at µs timescales. Here, we track the BBR-induced transfer of a prepared Rydberg state to its neighbors and use the evolution of these state populations to characterize the BBR field at the relevant wavelengths, primarily at 130 GHz. We use selective field ionization readout of Rydberg states with principal quantum number n∼30 in ^{85}Rb and substantiate our ionization signal with a theoretical model. With this detection method, we measure the associated blackbody-radiation-induced time dynamics of these states, reproduce the results with a simple semiclassical population transfer model, and demonstrate that this measurement is temperature sensitive with a statistical sensitivity to the fractional temperature uncertainty of 0.09 Hz^{−1/2}, corresponding to 26 K Hz^{−1/2} at room temperature. This represents a calibration-free SI-traceable temperature measurement, for which we calculate a systematic fractional temperature uncertainty of 0.006, corresponding to 2 K at room temperature when used as a primary temperature standard.